(untitled) (Pain medicine, 2016)
In its essence the human organism is an open, nonlinear, permanently and dynamically evolving biological system with appropriate hierarchical levels of organization. Currently pharmacotherapy takes the dominant position of complexes of curative and preventive measures. As a result of this, it is necessary for clinicians to have an idea of atomic and molecular hierarchical level of structural and functional organization of human organism, at which the mechanism ofpharmacological agents effect on it is realized. The theory of functional universal units gives the comprehension and the conception of: 1) principles, that underlie the structural and functional organization of human organism cells, realizing its physiological functions; 2) structural and functional organization of the system of human organism at the molecular, subcellular and cellular levels of its hierarchical structure; 3) basics of process realization of human organism physiological functions at the cellular level of its hierarchical organization; 4) causes, mechanisms and processes of human organism disease formation at the subcellular and cellular levels of its hierarchical, structural and functional organization; 5) system manifestation of certain nosological forms and multifocal effects of pharmacological remedies; 6) definition of the objective way of solving clinical problems.